2020
DOI: 10.3390/su12041642
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Winery Visitors in the Emerging Wine Regions of the North Central United States

Abstract: Most of the pioneering studies related to wineries were conducted in famous wine regions, the results of which were not especially applicable to the small and emerging wineries in the United States. These wineries rely heavily on visitors’ on-site purchases; this highlights the importance of understanding winery visitors’ behaviors. This study explored the sequential relationships among winery visitors’ pre-trip characteristics (motivation, wine involvement), on-site experiences (perceived value), and post-tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…This would lead to domestic consumption, which would entail the socioeconomic development of the territory while achieving wealth creation and the resulting added value in the local territory. The development of local businesses is key to the establishment of a business network that will lead to the aforementioned creation of wealth and value, which is already being done in other rural areas spread around the world [10,[66][67][68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would lead to domestic consumption, which would entail the socioeconomic development of the territory while achieving wealth creation and the resulting added value in the local territory. The development of local businesses is key to the establishment of a business network that will lead to the aforementioned creation of wealth and value, which is already being done in other rural areas spread around the world [10,[66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Gastronomy is a reflection of the cultural identity of a specific geographical area. This symbiosis between tourism and gastronomy promotes local produce consumption, territorial development and sustainability [10].…”
Section: Introductionmentioning
confidence: 99%
“…Positive and strong attachments are created by staying in a place for a long period [ 45 ]. Lee et al argued that tourists’ perceptions of positive experiences have a positive effect on tourists’ post-tour evaluations and help foster place attachment [ 46 ]. Wang et al found that perceived value has a significant positive effect on place attachment [ 47 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Liu et al found that emotional, functional, and social values in perceived value indirectly influence tourist loyalty through the mediating effect of well-being [ 39 ]. Lee et al argued that tourists’ perceived values of service and social well-being contribute to positive post-trip loyalty [ 46 ]. Thus, we propose that tourists’ perceived value is related to destination loyalty as follows:…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Apart from these, vineyards also attract footfalls through their resorts and restaurants which provides an intimate connection with tourists through involvement and learnings of various wine varietals, wine-making process and wine-food pairing (Lee et al , 2020). These project an elite and exclusive lifestyle which brings forth a differential aspect for both wine consumption and tourism (Gross et al , 2008).…”
Section: Literature Review and Framework Of Glocalized Wine Tourismmentioning
confidence: 99%